WAYS TO FORM MATHEMATICAL CONCEPTS AND IMAGINATIONS IN PRIMARY CLASS STUDENTS BASED ON FAIRY TALES (Journal of Universal Science Research, 2023)
this article presents ideas about the effectiveness of using fairy tales to help elementary school students achieve educational efficiency and deepen their learning of mathematics.